Synthesis, characterization and biological evaluation of mixed-ligand ruthenium(ii) complexes for photodynamic therapy. Issue 39 (21st September 2015) - Huang, Huaiyi; Zhang, Pingyu; Yu, Bole; Jin, Chengzhi; Ji, Liangnian; Chao, Hui
Abstract : We demonstrated the photodynamic therapy effect of mixed-ligand Ru(ii ) complexes.Ru1–Ru3 can kill cancer cells effectively upon light exposure through generating singlet oxygen and hydroxyl radical ions. Abstract : This study investigated the photodynamic therapy (PDT) and anticancer activity of mixed ligand Ru(ii ) terpyridyl complexes (Ru1–Ru3 ). The photophysical and photochemical properties, hydrophobic properties, DNA binding and DNA transcription inhibition abilities, cell uptake efficiency, cellular localization and photo-cytotoxicity were investigated.Ru1–Ru3 exhibited red luminescence between 670–710 nm and functioned as photo-sensitizers (PSs) by generating both singlet oxygen and radical ions. Without light activation, Ru1–Ru3 were located at the cytoplasm and were nontoxic to cells. However, upon light activation, Ru1–Ru3 exhibited significant photocytotoxicity. After PDT treatment, mitochondria alteration and nuclear membrane disruption occurred, which resulted in relocalization of the complexes from the cytoplasm to the nucleus. Moreover, high cellular oxidative stress caused cell necrocytosis after PDT treatment.